Research Study Of Management Information System (Regional Goods Management) In Pematang Serai Village, Langkat District - Galih Supraja; Junawan, Junawan; Annisa Fajariah Damanik (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to find out how effective the management of regional property is, to find out the procedures for managing regional property and to adjust the implementation of regional property management at the Village Government Pematang Serai, Langkat Regency. The form or method used in this research is descriptive with qualitative analysis. Meanwhile, data collection techniques were carried out through interview methods, documentation and direct observation. Data analysis used are data reduction, data presentation, and conclusion drawing. Based on the research conducted, results were obtained that analysis of fixed asset management (Regional Property) in Pematang Serai Village not yet running well seen from late administration and utilization, maintenance and administration, as well as the implementation of asset management, are still not running optimally as stated in government regulations and also obstacles in managing fixed assets.